Multiple births conceived by assisted reproductive technology in Korea - Young Sil Park; Sun Hee Choi; Kye Shik Shim; Ji Young Chang; Won Ho Hahn; Yong Sung Choi; Chong-Woo Bae (Korean Pediatric Society, 2010)
PurposeThe recent trends of multiple births (MBs) conceived by assisted reproductive technology (ART) in Korea were analyzed as well as the relationship with maternal age, especially advanced maternal age.MethodsData were obtained from the Korean Statistical Information Service and annual ART reports from the ART committee of the Korean Society of Obstetrics and Gynecology.ResultsMBs increased from the early 1990s; there was a 275% increase by 2008. The number of total live births was 448,153 and MBs accounted for 10,767; the MB rate was 24.0% in 2006. Among 2,326 deliveries conceived by ART, multiple deliveries accounted for 786 (33.8%). The total number of live births with ART was 3,125 and 1,585 (50.7%) of them were MBs. During 2006, 14.7% of the entire MBs in Korea were associated with ART. The proportion of women of advanced maternal age was much higher in the ART group than in the total live birth group.ConclusionMBs in women of advanced maternal age have been increasing in Korea with the use of ART. The results of this study showed that ART was a significant factor associated with the increase in MBs in Korea.